Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Etnomatematika Di SMP Negeri 1 Sukadana - Devi, Aprilia; Mustika, Juitaning (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2023)
This developmental research aims to produce instructional material (LKPD) based on ethnomathematics in traditional Lampung dance to enhance the understanding of lines and angles based on validity and practicality. The research design is development or research and development, designed using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. However, during the implementation phase, only limited testing was conducted. The instruments used in this research were a questionnaire for expert content and media validation to assess the instructional material’s validity. In contrast, a questionnaire for student responses was used to determine the practicality of the instructional material. The research results indicate the quality of the developed product, which received a highly valid rating from content and media experts. As for practicality, based on the questionnaire responses from 9 students at SMP Negeri 1 Sukadana, the overall average score obtained was 3.58, indicating that the developed instructional material falls under the category of highly practical.